Agricultural education of the future: the Malaysian perspective - Wan Harun, Wan Sulaiman (1996)
Inspite of continuous growth over the last four decades, the agriculture sector's successes pale in comparison with those of manufacturing and services sectors. Problems and circumstances contributing to this disparity include, among others, limited land for expansion of land-based agriculture, loss of quality agricultural land to urbanisation and industry, and trade and fiscal measures which favour industry thus drawing resources away from agriculture. The National Agriculture Policy, 1992-2010 was thus founded with the overriding aim of maximizing income through optimal utilization of resources and with the objectives of achieving a balanced development between agriculture and the other sectors of the economy, integration of agriculture with the rest of the economy, achieving a higher mlevel of expansion and development of the food industry and ensuring sustainable development. From the global context, agriculture has entered anew, consumer-driven era that requires a transition from a commodity-based to a product-based agriculture, nations to assume greater responsibility for feeding their own populations, ability to respond to consumer needs and awareness and ability to capitalize on rapidly changing biotechnology and information technology with promises from a more liberal and fairer world agricultural trade. Hardly any of the current degree programmes in agriculture adequately prepare graduates for the many and serious problems and issues confronting agriculture. An added dimension in the reassessment of agricultural education is the liberalization of higher education and the employment market trend of seeing the development of well-educated and skillful graduates as being of a greater imperative than a higher degree of specialization. Responding to the imperatives for revitalizing agricultuaral education, the Faculty of Agriculture, Universiti Pertanian Malaysia undertook a major overhaul in their degree programmes. A new broad-based programe, Bachelor of Science in Bioindustry wasintroduced in. July 1996 to give due recognition to agriculture as an industry, i.e., an industry founded on biotic and living organism. Bioindustry is involved with the economic management of systems which exploit the biotic potential of organisms within the system.This includes levels of biological processes, bionomics, economics and utilization. The curriculum aims at giving a holistic approach to an understanding of biotic factors, their physiology and relationship to environmental factors and the potential exploitation in sustainable production systems. The choice of courses, previously limited in scope to agricultural sciences only, is made wider covering global, environment and industryfocused issues to suit varying interests of students. The new programme has so far received favourable response from students and industry.